Teaching Phraseological Units and Their Problems (Journal of Pedagogical Inventions and Practices, 2022)
Phraseological units absorb values of the ages in which it lives. The problem of understanding the meaning of a phraseological unit is linked with a possibility of increasing our knowledge about the world diachronically. The authors underline the importance of phraseological studies as it demonstrates the interrelation between the language and the society. The role of phraseological units as specific structures in forming vocabulary and linguacultural competence of students is very significant because they encapsulate a national, country’s cultural outlook. Usagebased theories of language learning suggest that phraseology must be studied as a part of vocabulary. Teaching phraseology is a part of cultural approach in foreign teaching methodology and arranging vocabulary studying though structure of component meaning is linguistic approach. This article begins by establishing a theoretical framework to help find the answer to the question: ‘‘what do the words in a phraseological unit mean?’’. From there, major phraseological concepts on the problem are reviewed. Complex methodology is applied: method of phraseological identification, semantic analysis. Finally, the article concludes with a discussion of four types of wordcomponents in phraseological units: real words; potential words; “former” words; “ghostwords and possible paths for future research